Linking Accounting Information and Internal Controls to Sustainable Performance: Evidence on the Mediating Role of Management Control Systems - Sinarasri, Andwiani; Murniningsih, Rochiyati (Jurnal Analisis Bisnis Ekonomi, 2024)
Organizational sustainability is an important issue in the management of Islamic Microfinance Institutions (IMFIs) because these institutions are not only required to achieve economic performance, but also to fulfill social and institutional responsibilities in a sustainable manner. This study examines the influence of the Accounting Information System (AIS), Internal Control System (ICS), and Management Control System (MCS) on Sustainability Performance among 89 IMFIs in Central Java, Indonesia. Data were analyzed using Smart PLS, and the findings reveal that AIS has not been able to support the effectiveness of MCS, thereby failing to contribute to the achievement of sustainability performance. In contrast, ICS has a positive effect on MCS, and MCS mediates the relationship between ICS and sustainability performance. The study concludes that ICS plays a more strategic role than AIS in enhancing sustainability performance within IMFIs. The primary theoretical contribution of this study lies in highlighting the mediating role of MCS in translating the function of ICS as an internal control mechanism into improved sustainability performance outcomes. Practically, this study provides valuable implications for the management of IMFIs by emphasizing the importance of strengthening ICS and developing sustainability-oriented MCS. The findings indicate that improving the quality of supervision, risk management, and integrated performance evaluation can support IMFIs in achieving more sustainable economic, social, and institutional performance. Furthermore, this study emphasizes that the implementation of AIS should be optimized not merely as an administrative tool, but also as a strategic information resource for managerial decision-making processes.